Parques Urbanos de São Carlos (SP): percepções sobre seus usos, conexões e melhorias para a gestão urbana - Pereira, Renan Cesar dos Santos (2024)
Urban Parks are educational spaces, with environmental, social, aesthetic and cultural benefits, in which it is possible to develop environmental education and the responsible appropriation of reality through transformative actions, and it is necessary to know the perception of those who frequent these spaces. This study aims to identify the perception of the population that uses Urban Parks in São Carlos (SP) regarding functions, uses, connections between parks and community involvement, seeking to indicate subsidies for the advancement of the management of green spaces in the city. A survey of 5 laws and decrees referring to the administrative structure responsible for the management of urban parks was carried out, followed by 27 documents referring to the normative legal framework on green areas and urban parks, examining environmental education, functions and social participation, and finally, questionnaires were applied in 6 urban parks in the city, analyzing the functions, uses, connectivity, social participation and suggestions for improvements in the spaces studied. The results indicate that administrative functions regarding green spaces in the city are divided into at least three sectors of three different departments, which results in fragmentation and overlapping responsibilities. The notable advancement of the normative framework on this topic involves the publication of decrees to turn public areas into urban parks, although still without adequate infrastructure or the definition of issues such as connections between green areas or which public body is responsible for environmental education activities. Of the 180 respondents, 50.3% are female, the dominant age group was between 26 and 45 years old and they prefer to visit parks close to their homes. The promotion of leisure activities is the function most perceived (by 137 people), followed by environmental conservation (49), the generation of income (39), the contribution to people's health (37), a more pleasant climate (33) and the encouragement of educational activities (26). The suggestions for improvements collected mostly refer to structural issues, such as maintenance and improvement of equipment and requalification of sports practice spaces. In addition to this, there is a demand for more leisure options and better health and education conditions. It is concluded that urban parks have potential, as educational, leisure and social spaces, which can be better utilized through the continued advancement of legislation.